2019
DOI: 10.1371/journal.pone.0215030
|View full text |Cite
|
Sign up to set email alerts
|

Pilots and athletes: Different concerns, similar concussion non-disclosure

Abstract: Objectives Concussion non-disclosure research has focused almost exclusively on athletes. The focus on athletic populations has been sensible considering athletes’ demonstrated susceptibility to sustaining and concealing concussions. Nevertheless, the habitual use of athletic populations has allowed researchers and practitioners to omit the development of generalized perceived costs and perceived rewards as critical determinants of concussion self-disclosure. We hypothesized that perceiving concus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…A cadet with a previous concussion may have increased concussion knowledge that alters his or her disclosure behavior. For example, Foster et al 27 found that US Air Force cadets were concerned that having a concussion would prohibit them from becoming pilots. Thus, because concussions are perceived to influence military placement, disclosure was also a concern among cadets.…”
Section: The Symptom Durationmentioning
confidence: 99%
“…A cadet with a previous concussion may have increased concussion knowledge that alters his or her disclosure behavior. For example, Foster et al 27 found that US Air Force cadets were concerned that having a concussion would prohibit them from becoming pilots. Thus, because concussions are perceived to influence military placement, disclosure was also a concern among cadets.…”
Section: The Symptom Durationmentioning
confidence: 99%
“…A study involving United States Air Force Academy cadets provides a nice example. 17 Women reported greater willingness to self-disclose concussions than did men. A subsequent analysis revealed that this gender effect occurred because a greater portion of men intended to become pilots, and these future pilots were concerned that disclosure could influence their careers.…”
Section: The Psychological Foundation Of Concussion Non-disclosurementioning
confidence: 97%
“…A subsequent analysis revealed that this gender effect occurred because a greater portion of men intended to become pilots, and these future pilots were concerned that disclosure could influence their careers. 17 In other words, there was a gender effect, but it was rooted in the perceived direct costs associated with wanting to become pilots.…”
Section: The Psychological Foundation Of Concussion Non-disclosurementioning
confidence: 99%
“…Perceptions of the negative consequences of injury disclosure are targets for future studies and public health initiatives. 42 Similarly, prevention, across the spectrum, is insufficient. 43 With attention focused on building comprehensive concussion programs, such as the CCM, education, outreach, and research will continue to further promote concussion awareness and management.…”
Section: Public Health Concern-need For Morementioning
confidence: 99%